Analisis Kompetensi Profesional Guru Yang Tidak Sesuai Mata Pelajaran Di SMP Muhammadiyah 1 Sampit - Nina Yusac Rahmadani; Mohammad Syahri; Mochammad Agus Krisno Budiyanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe (1) the Professional competence of teachers who do not match subjects in SMP Muhammadiyah 1 Sampit. (2) The impact of teacher teaching that is not by the subjects at SMP Muhammadiyah 1 campsite. (3) Strategies for enhancing Teacher Professional Competence that does not match subjects in SMP Muhammadiyah 1 campsite. The research method used is a qualitative descriptive approach through observation, interview, and documentation techniques. Data validity is used by the source triangulation technique. The results showed that there were problems in Teacher Professional Competencies that did not match subjects in SMP Muhammadiyah 1 Sampit Central Kalimantan including (1) The ability of teachers to master the material, respond to questions, create learning conceptual frameworks, apply learning indicators, develop learning materials and use learning diversity of learning materials. (2) Teacher teaching that is not by the subject matter has an impact on classroom management and the use of learning resources in the classroom. (3) Strategies for enhancing Teacher Professional Competence that is not in line with subjects in Muhammadiyah 1 Sampit Middle Kalimantan Middle School include magazine training and Internet Media.Keywords: Teacher, Professional competence, Subjects are not suitable Abstrak: Penelitian ini bertujuan untuk mendeskripsikan (1) Kompetensi profesional guru yang tidak sesuai mata pelajaran di SMP Muhammadiyah 1 Sampit. (2) Dampak pengajaran guru yang tidak sesuai dengan mata pelajaran di SMP Muhammadiyah 1 sampit. (3) Strategi peningkatan Kompetensi Profesional Guru yang tidak sesuai mata pelajaran di SMP Muhammadiyah 1 sampit. Metode penelitian yang digunakan adalah pendekatan deskriptif kualitatif melalui teknik observasi, wawancara dan dokumentasi. Keabsahan data digunakan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa ditemukan masalah dalam Kompetensi Profesional Guru yang tidak sesuai mata pelajaran di SMP Muhammadiyah 1 Sampit Kalimantan Tengah meliputi (1) Kemampuan guru dalam hal menguasai materi, menyikapi pertanyaan, membuat kerangka konsep pembelajara, mengaplikasikan indikator pembelajaran, mengembangkan materi pembelajaran dan menggunakan keragaman bahan pembelajaran. (2) Pengajaran Guru yang tidak sesuai mata pelajaran berdampak terhadap pengelolaan kelas dan penggunaan sumber belajar didalam kelas. (3) Strategi peningkatan Kompetensi Profesional Guru yang tidak sesuai mata pelajaran di SMP Muhammadiyah 1 Sampit Kalimantan Tengah meliputi pelatihan majalah serta Media Internet.Kata Kunci: Guru, Kompetensi profesional, Mata pelajaran tidak sesuai